Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm quite new to this whole topic and so I don't know how get a grip on this question:

Let $G$ be a group and $U,V$ two subgroups. Denote by $[U,V]$ the subgroup of $G$ generated by $[u,v]=uvu^{-1}v^{-1}$ with $u \in U, v \in V$. Show: $U\times V \rightarrow G$, $(u,v) \mapsto [u,v]$ is bilinear $\Leftrightarrow$ [U,V] is contained in the centre of the subgroup of $G$, that is generated by $U$ and $V$

I'd be happy for any hint and help :)

share|cite|improve this question
up vote 0 down vote accepted

Hint: $[a,bc] = [a,b][a,c]^b$ and $[ab,c] = [b,c]^a [a,c]$. Here, $x^y = yxy^{-1}$ denotes conjugation.

share|cite|improve this answer


$$(u,v)\to [u,v]\,\,\text{bilinear}\,\,\Longleftrightarrow (u_1u_2,v)=(u_1,v)(u_2,v)\,\,,\,\,(u,v_1v_2)=(u,v_1)(u,v_2)$$

where we're considering the operation in $\,G\,$ to be multiplicative.

But using the basic property of commutators ($\,[ab,c]=[a,c]^b[b,c]\,$), we get:


Try now to take it from here...

share|cite|improve this answer
OK, so first I try to show $(u_{1}u_{2},v)=(u_{1},v)(u_{2},v) \Leftrightarrow [U,V]$ contained in centre of the subgroup...(see above) (So the "\Rightarrow" part) (i): $(u_{1}u_{2},v)\mapsto [u_{1}u_{2},v]=[u_{2},v]^{u_{1}}[u_{1},v]=u_{1}u_{2}v u_{2}^{-1}u_{1}^{-1}v^{-1}$. (ii): $(u_{1},v)(u_{2},v)\mapsto [u_{1},v][u_{2},v] = u_{1}v u_{1}^{-1}v^{-1}u_{2}v u_{2}^{-1}v^{-1}$. Now $u_{1}u_{2}v u_{2}^{-1}u_{1}^{-1}v^{-1}$ shell be the same as $u_{1}v u_{1}^{-1}v^{-1}u_{2}v u_{2}^{-1}v^{-1}$. $u_{1}u_{2}v u_{2}^{-1}u_{1}^{-1}v^{-1}=u_{1}v u_{1}^{-1}v^{-1}u_{2}v u_{2}^{-1}v^{-1}$ (no char left) – Luca Oct 7 '12 at 13:22
I don't think you have to open up the commutator parentheses, as this may make thing messier. Think of this as $$x=x^a\Longrightarrow ax=xa\Longrightarrow x\in C_G(a)\,\,...$$ – DonAntonio Oct 7 '12 at 13:26
then i multiply both sides from left by $u_{1}$ and from the right with $v$.\\ $u_{2}vu_{2}^{-1}u_{1}^{-1} = vu_{1}^{-1}v^{-1}u_{2}vu_{2}^{-1}$\\ $\Leftrightarrow u_{1} (u_{2}vu_{2}^{-1}v)u_{1}^{-1}(u_{2}v^{-1}u_{2}^{-1}v){-1} = e$\\ So we see that the expression in the brace is an element of [U,V] and lies in the centre of U (?) And this analogous for $v_{1},v_{2}$ shows it lies in the centre of V(?) Here I know I'm missing something... – Luca Oct 7 '12 at 13:35
ah, sorry saw your comment too late! – Luca Oct 7 '12 at 13:36

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.